Factors associated with subcentimeter pulmonary nodule outcomes followed with computed tomography imaging in oncology patients. (2020) - de Morais, André Queiroz; da Silva, Thiago Pereira Fernandes; Braga, Juliana Cristina Duarte; Teixeira, Diogo Fábio Dias; Barbosa, Paula Nicole Vieira Pinto; Haddad, Fábio José; Gross, Jefferson Luiz; Santana, Pablo Rydz Pinheiro; Hochhegger, Bruno; Marchiori, Edson; Guimarães, Marcos Duarte
Highlights: PNs with irregular, lobuled or spiculated margins exhibited faster growth than PNs with regular, smooth margins. Malignancy was significantly associated with male gender, a colorectal cancer diagnosis and advanced stage disease. Oncologic patients should have an individualized CT follow-up strategy, as the rate of malignant pulmonary nodules is higher than in the general population. Abstract: Introduction: Technological advancements in computed tomography (CT) have enabled the frequent detection of small pulmonary nodules (PNs), especially in patients with an oncologic history. It is important the malignant versus benign etiology of PNs be determined. The aim of the present study was to evaluate the behavior and clinical/radiological characteristics of subcentimeter PNs detected by CT in oncologic patients. Methods: An observational, longitudinal, retrospective and single-center study was conducted with a sample of 100 patients with a diagnosis of a primary malignant solid tumor outside of the lungs who developed indeterminate subcentimeter PNs (n = 251) detected on consecutive thoracic CT scans from 2015 to 2017. Follow-up CTs for each patients were examined in each of three periods (0–3 months, 3–6 months, and 6 months to 1 year). Results: In our study sample, 28 patients (28 %) showed one or more signs suspicious of pulmonary metastasis, including ≥50 % PN growth, nodule growth followed by size reduction in patients undergoing chemotherapy, and the appearance of multiple nodules. The majority (56 %) of the PNs were detected during the 3–6-month follow-up CT scan. PNs with irregular, lobuled, or spiculated margins exhibited faster growth than PNs with regular, smooth margins. Malignancy of PNs was found to be significantly associated with being male, a primary colorectal cancer diagnosis, and advanced stage disease. Conclusion: Our findings reinforce the necessity of an individualized CT follow-up strategy for patients with an oncologic history, as well as the importance of early nodule screening, with the inter-scan interval being dependent on the primary neoplasm.